Production of Brachiaria decumbens Grass at Various Levels of Drought Stress Treatment - Aulia FIkri Ariq Putra; Nevy Diana Hanafi; Hamdan .; Ma'ruf Tafsin; Edhy Mirwandhono (Jurnal Peternakan Integratif, 2017)
Abstract. This study aims to determine effects of production of Brachiaria decumbens grass on different drought stress treatments. Research was conducted at the Greenhouse Faculty of Agriculture University of North Sumatera from  Desember 2016 until April 2017. The design used was Completely Randomized Design (CRD), with three treatments and seven replications. The treatment consisted of three levels of drought stress which were  control (100% field capacity=fc), medium drought stress  (25% fc), and heavy drought stress (50% fc). The variable were fresh weight production, dry weight production and plant height. The results showed that drought stress treatment control (100% fc) significantly (P<0,05) affect fresh weight production, dry weight production, but not plant height. It is concluded that increasing water volume of field capacity increase production Brachiaria decumbens grass.